Flagella overexpression attenuates Salmonella pathogenesis. - Xinghong Yang; Theresa Thornburg; Zhiyong Suo; SangMu Jun; Amanda Robison; Jinquan Li; Timothy Lim; Ling Cao; Teri Hoyt; Recep Avci; David W Pascual (PLoS ONE, 2012)
Flagella are cell surface appendages involved in a number of bacterial behaviors, such as motility, biofilm formation, and chemotaxis. Despite these important functions, flagella can pose a liability to a bacterium when serving as potent immunogens resulting in the stimulation of the innate and adaptive immune systems. Previous work showing appendage overexpression, referred to as attenuating gene expression (AGE), was found to enfeeble wild-type Salmonella. Thus, this approach was adapted to discern whether flagella overexpression could induce similar attenuation. To test its feasibility, flagellar filament subunit FliC and flagellar regulon master regulator FlhDC were overexpressed in Salmonella enterica serovar Typhimurium wild-type strain H71. The results show that the expression of either FliC or FlhDC alone, and co-expression of the two, significantly attenuates Salmonella. The flagellated bacilli were unable to replicate within macrophages and thus were not lethal to mice. In-depth investigation suggests that flagellum-mediated AGE was due to the disruptive effects of flagella on the bacterial membrane, resulting in heightened susceptibilities to hydrogen peroxide and bile. Furthermore, flagellum-attenuated Salmonella elicited elevated immune responses to Salmonella presumably via FliC's adjuvant effect and conferred robust protection against wild-type Salmonella challenge.